Project-Based Learning for Mechanical Engineering Students in the Emergency Remote Teaching - Dewanti Ratna Pertiwi; Maria Asumpta Deny Kusumaningrum (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Covid-19 has changed a lot of life sectors, including education. The government’s policy to carry out emergency remote teaching (ERT) immediately switches the teachers’ and lecturers’ plans on successful classroom activities. One of the classroom’s activities is project-based learning (PBL). With several limitations, challenges should be taken on so that designing simple but meaningful projects can facilitate project-based learning. Thus, some adaptations should be made since some students are economically impacted. Online learning modes, either synchronous or asynchronous were held to communicate the project. A descriptive qualitative research method was employed by involving two classes of mechanical engineering students. Data were collected from learning platforms observations, interviews with students’ representatives, and questionnaires administered to all students. The project was conducted in four stages; beginning the infographic project, developing the project, closing the project, and evaluating the project. The research indicated that the students completed and engaged in the project successfully through some problems that came up, mainly when the students had to have group work and communicate using internet media since most students were back home with various internet connection access. However, some assessable applications were employed so that the project was well accomplished. In conclusion, conducting a PBL in emergency remote teaching was successfully conducted with some simple available and accessable applications since the students’ conditions varied significantly.